Comunicação e privacidade de dados na internet: estudo sobre as percepções do usuário à luz da LGPD - Lourenço, Simões, Alessandra (2021)
The evolution of the means of communication allowed the exercise of the right to communication faster and with an exponential reach through the internet. Citizens now have a voice, interacting through texts, links, videos and images, sharing updates on their personal and professional lives, news and other events. However, the volume of this information in the digital space ended up calling the attention of public and private organizations, in addition to malicious people. Information becomes the target of monitoring, leakage and even misuse, violating the right to privacy of connected citizens, who are not always aware of these facts and their consequences. The subject gained the agenda and became a discussion after several scandals on the subject gained the attention of the media, such as the Snowden and Cambridge Analytica case. Even though the protection of privacy was guaranteed by laws and other regulations around the world, something more specific to the digital world was missing. Then, in 2018, the General Data Protection Regulation (GDPR) becomes effective in the European Union, which regulates the European law on the protection of personal data and serves as the basis for the emergence of other laws worldwide, such as the General Law of Data Protection in Brazil (LGPD). Thus, this study aims to verify whether the concern and protection of privacy are influenced by the factors negative experience of privacy, trust in regulators and the perception of reward. To carry out the study in question, this work consists of a literature review, a questionnaire and statistical analysis of the responses. In the literature review, the following themes were addressed: human rights and the right to communication, communication and digital media; data leakage and misuse; the issue of privacy and personal data; specific regulations; concern for privacy; privacy protection; reward perception; negative privacy experience; and trust in regulators. The questionnaire was developed from other similar studies, such as the one carried out by Smith et al. (1996) and by Kininmonth et al. (2018), making minor adaptations to existing issues. Therefore, this research is also confirmatory, as it starts from constructs, or factors, already studied in previous hypotheses. Questions of a sociodemographic nature were also included, as a way to analyze and frame the profile of respondents to the objectives of this research. The application of the survey questionnaire was carried out online through an electronic form, with distribution by email, social networks and other communication channels. The sample consists of 304 valid answered questionnaires and the analysis of the proposed research model resulted in the confirmation of the hypotheses: the perception of reward negatively influences the protection of privacy, the perception of reward negatively influences the concern with privacy and the trust in regulators negatively influences privacy concerns. The hypotheses were not confirmed: concern for privacy positively influences privacy protection and trust in regulators negatively influences privacy protection.(AU)